Development and Evaluation of Functional Instant Powder Drink from a Combination of Turmeric Rhizome (Curcuma longa L.) and Purple Sweet Potato Tubers (Ipomoea batatas L.) - Mida Hamidah; Adilla Nurafdilla Solihah; Nur Laili Dwi Hidayati; Nopi Rantika (Faculty of Mathematic and Natural Science, Garut University, 2026)
This study aims to develop and evaluate a functional instant powder drink formulated from a combination of Turmeric Rhizome (Curcuma longa L.) and Purple Sweet Potato Tuber (Ipomoea batatas L.) as a practical herbal drink that has antioxidant potential. The study was conducted through several stages, including sample preparation, phytochemical screening, instant powder formulation, physical evaluation, identification of curcumin compounds using Thin Layer Chromatography (TLC), and antioxidant activity testing using the DPPH method. Physical evaluation included organoleptic tests, flow rate, angle of repose, water content, pH, viscosity, solubility, sedimentation, stability, and hedonic tests. The results showed that the combination of Turmeric Rhizome and Purple Sweet Potato contains secondary metabolites in the form of flavonoids, alkaloids, saponins, tannins, and phenolic compounds that have potential as antioxidants. The resulting instant powder has good physical characteristics and meets the evaluation requirements for instant powder preparations. Identification using TLC showed the presence of curcuminoid compounds, namely curcumin, demethoxycurcumin, and bisdemethoxycurcumin, in the formulation. Antioxidant activity testing using the DPPH method showed that the turmeric extract had very strong antioxidant activity with an IC50 value of 19.786 ppm, while the instant powdered drink formulation showed weak antioxidant activity with an IC₅₀ value ranging from 255,743–321,101 ppm. The decrease in antioxidant activity is thought to be due to the heating process during powder production, which results in the degradation of some of the active compounds. Therefore, an instant powdered drink combining Turmeric Rhizome and purple sweet potato has the potential to be developed as a natural functional beverage with good physical properties and antioxidant activity.